2010
DOI: 10.1348/000709910x498544
|View full text |Cite
|
Sign up to set email alerts
|

Students' daily emotions in the classroom: Intra‐individual variability and appraisal correlates

Abstract: The within-student variability in emotions and appraisals clearly demonstrates the adaptability of students with respect to situational affordances and constraints in their everyday classroom experiences. The significant covariations between the appraisals and emotions suggest that within-student variability in emotions is systematic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
56
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(63 citation statements)
references
References 32 publications
5
56
1
1
Order By: Relevance
“…Helmke, 1993;Wigfield & Eccles, 1989 ), secondary school students (e.g. Ahmed et al, 2010;Gläser-Zikuda et al, 2005;Hagenauer & Hascher, 2010) and students in further and higher education (e.g. Christie et al, 2008;Grieder, 2006), but also explorations of the emotions of teachers (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Helmke, 1993;Wigfield & Eccles, 1989 ), secondary school students (e.g. Ahmed et al, 2010;Gläser-Zikuda et al, 2005;Hagenauer & Hascher, 2010) and students in further and higher education (e.g. Christie et al, 2008;Grieder, 2006), but also explorations of the emotions of teachers (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…(Efklides & Violet, 2005;Linnenbrink, 2006;Schutz & Lavehart, 2002;Schutz & Pekrun, 2007 Ahmed et al, 2010). Similarly, Ahmed et al (2010) in a study of emotions in the classroom concluded that learners' competence and value-belief appraisals determined the nature of achievement emotions. They found gender differences in mathematics related emotions.…”
Section: Emotional Self-concept and Academic Achievementmentioning
confidence: 99%
“…The emotions were however, context specific according to the control-value theory of achievement emotions. (Pekrun, 2006in Ahmed et al, 2010. Control was about whether the learner felt able to tackle a curricular task while value referred to whether the learner perceived achievement as important to him or her.…”
Section: Emotional Self-concept and Academic Achievementmentioning
confidence: 99%
See 2 more Smart Citations